A decade after the first Pucciniales genomes: A bibliometric snapshot of (post) genomics studies in three model rust fungi - Petre, Benjamin; Duplessis, Sébastien (Frontiers in Microbiology, 2022)
Pucciniales (rust fungi) are one of the largest fungal order of plant pathogens. They collectively infect key crops such as wheat and soybean, and threaten global food security. In the early 2010s, the genome sequences of three rust fungi were released: Melampsora larici-populina (the poplar leaf rust fungus), Puccinia graminis f. sp. tritici (the wheat stem rust fungus), and Puccinia striiformis f. sp. triciti (the wheat stripe rust or wheat yellow rust fungus). The availability of those genomes has forwarded rust biology into the post-genomic era, sparking a series of genomics, transcriptomics, in silico, and functional studies. Here, we snapshot the last ten years of post-genomics studies addressing M. larici-populina, P. graminis f. sp. tritici, and/or P. striiformis f. sp. tritici. This mini-review notably reveals the model species-centered structure of the research community, and highlights the drastic increase of the number of functional studies focused on effectors since 2014, which notably revealed chloroplasts as a central host compartment targeted by rust fungi. This mini-review also discusses genomics-facilitated studies in other rust species, and emerging post-genomic research trends related to fully-phased rust genomes.